Oceanografia de estuários amazônicos: rio Curuçá (Curuçá-PA) - SILVA, Helanir Furtado da (2020)
This study present aimed to characterize and evaluate the Curuçá River estuary (Curuçá city -PA) through physical, chemical, bathymetric and sedimentological parameters. The Curuçá’s estuary is located in northeastern of Pará, has a climate considered very humid with temperatures ranging around 27ºC, small temperature variation, with annual rainfall abundant that exceed 2.000mm, the wettest months are January to June and the less rainy months from July to December; presenting macrotides semidiurnal extend by 5.7m.The data generated were integrated to characterize physical and chemical oceanographic parameters of the estuary. The sample collect occurred during the rainy season (march/2013), in two fixed strategic points where we observed the change of the tide, analysis of surface currents and tides of the physic-chemical properties, beyond the bathymetric survey and sediment along the estuary. The results obtained in the Curuçá’s estuary showed that during the observation period the behavior of the curve tidal on Curuçá river showed that it is configured as the type macrotides semidiurnal tide with values between 4.71m to -0.05m.The surface current showed values of 0.86m/s at low tide and 0.12m/s in the stuff of low tide, and the average was 0.49m/s. The surface sediments classify by the average parameter presented as particle size fraction predominantly very fine sand, the selection was ranked in: very poorly selected, poorly selected, well selected, very well selected and moderately selected, presenting very positive asymmetry, roughly symmetric, negative and very negative. The kurtosis was classified as leptokurtic, platykurtic, leptokurtic and mesokurtic. According to the diagram Sherpard’s the sediments of 17 samples were mostly classified into sandstone and according to the diagram Pejrup the hydrodynamic environment has moderate to high.In the estuary was observed values of temperature between 28.78°C to 30.84°C, pH from 7.57 to 8.12, conductivity from 30201.4μs/cm at 31951.6 μs/cm and salinity 19.06 to 19 82, dissolved oxygen 4.32ml/L to 4.87ml/L and total dissolved solids 15100ppm to 15976.6ppm.